Effect of Mn and Pb promoters on the performance of Cu/ZnO-catalyst in Co2 hydrogenation to methanol - Tasfy, S.F.H. (Trans Tech Publications Ltd, 2014)
The influences of Mn or Pb promoters on the catalytic performance of Cu/ZnO-SBA-15 catalyst in the methanol synthesis from CO2 hydrogenation were studied. The catalytic performances of the prepared catalysts were investigated in a stirred high pressure reactor under conditions of T = 483K, P = 2.25 MPa, and H2:CO2 = 3:1 (volume ratio). The experimental results showed that the promoted catalysts exhibited higher catalytic performance. The Mn promoted catalyst resulted in 36 of CO2 conversion and 67 of methanol selectivity, whereas the unpromoted catalyst showed 26 of CO2 conversion and 58 of methanol selectivity. Â© 2014 Trans Tech Publications, Switzerland.